2019
DOI: 10.1002/anie.201907909
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Melting of Oligonucleotides by Oscillating Salt Concentrations Triggered by Microscale Water Cycles Inside Heated Rock Pores

Abstract: To understand the emergence of life,abetter understanding of the physical chemistry of primordial non-equilibrium conditions is essential. Significant salt concentrations are required for the catalytic function of RNA. The separation of oligonucleotides into single strands is adifficult problem as the hydrolysis of RNAb ecomes al imiting factor at high temperatures.S alt concentrations modulate the melting of DNAo r RNA, and its periodic modulation would enable melting and annealing cycles at lowt emperatures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…The Sutherland group has reported that pH fluctuations can drive RNA separation (Mariani et al, 2018a), but this does not address the problem of rapid strand annealing following the return of the pH to more neutral values. The Braun group has recently shown that wet-dry cycles inside heated rock pores triggering salt concentration fluctuations can also lead to strand separation (Ianeselli et al, 2019). Although these latter two approaches are simple and prebiotically plausible, up till now no demonstration of non-enzymatic RNA copying has been reported with these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The Sutherland group has reported that pH fluctuations can drive RNA separation (Mariani et al, 2018a), but this does not address the problem of rapid strand annealing following the return of the pH to more neutral values. The Braun group has recently shown that wet-dry cycles inside heated rock pores triggering salt concentration fluctuations can also lead to strand separation (Ianeselli et al, 2019). Although these latter two approaches are simple and prebiotically plausible, up till now no demonstration of non-enzymatic RNA copying has been reported with these methods.…”
Section: Introductionmentioning
confidence: 99%
“…We also tried to get kinetic measurements of the same samples by using Eva Green intercalation dye in temperature jump experiments with a thermocycler (SI‐10). Although such measurements were successful for kinetic FRET measurements, [40] the intercalating dye was unfortunately not suitable for kinetics measurements of the short DNA strands in our hands. The KMST‐measured on‐rates showed weak to no dependence on strand length and increased linearly with salt concentration by (1.9±0.2)×106M-1s-1×PBS (Figure 4 a,b).…”
Section: Resultsmentioning
confidence: 98%
“…Experimental models of such fluctuating environments have been studied extensively by Braun et al (Ianeselli et al 2019;Morasch et al 2019;Salditt et al 2020). Volcanic or impact related hydrothermally active settings have the potential to provide such rapidly fluctuating environments in nature.…”
Section: Emergence and Stability Of Virtual Circular Genomesmentioning
confidence: 99%